Wind-driven rain as a bioclimatic factor affecting the biological colonization at the archaeological site of Pompeii, Italy. (October 2018) - Traversetti, L.; Bartoli, F.; Caneva, G.
Abstract: The weathering role of Wind-Driven Rain (WDR) on buildings is widely recognised from a physical point of view, but the influence of WDR on Biological Growth (BG) on stone materials to cause biodeterioration is still not well studied. Following our previous results from the Roman area, the UNESCO site of Pompeii for its importance was selected to further test relationships between WDR and BG. We collated and analysed climatic data (rainfall, direction and intensity of winds) between 2010 and 2015 to delineate the thermo-pluvial diagram and extrapolate Dominant Winds (DW) and WDR. Data on BG, consisting mainly of cyanobacteria, algae and lichens, were also collected through sampling, direct observations and analysis of high-quality photos. The climatic elaborations highlighted a dominance of the West wind influencing WDR. The BG was more prominent on the northern and western exposures, while it was considerably less extensive on the southern walls. Our results also showed that water from WDR, together with the lower temperature in the northern exposure and poor ventilation, can all affect wetness and had a profound role in the promotion of BG. Our analyses suggest that the protection of building walls should be different according to the exposure conditions in the formulation of preventive strategies for conservation. Highlights: Wind driving rain (WDR) highly affects the biological growths (BG) on vertical surfaces. In Pompeii, a dominance of western winds for Dominant winds (DW) and WDR occurs. In Pompeii, the trend of BG on vertical surfaces shows two peaks in W and in N. WDR, high temperatures, and ventilation, need to be considered to evaluate the risks of BG. A differential protection of walls can be carried out considering such data.